Synthesis and Characterization Complexes of Cobalt(II), Nickel(II), Copper(II) and Palladium with [N'-{2-(4-isobutyl-phenyl)-propionyl} pyridine-4-carbohydrazide] - Modher Y. Mohammed; Ayad S. Hameed; Adnan A. Hamada (Tikrit Journal of Pure Science, 2023)
This research concern with the metal complexes of the ligand [N'-{2-(4-isobutyl-phenyl)-propionyl}pyridine-4-carbohydrazide]  with Co(II), Ni(II) , Cu(II) and Pd(II) have been synthesized and characterized by atomic absorption , infrared, electronic spectra, molar conductivity and magnetic moment measurements. On the basis of the data obtained from the above measurements, the ligand act as a neutral bidentate and the octahedral structures are proposed for the Co(II), Ni(II) and Cu(II) while the square planer structures are assigned to Pd(II) complexes.